Pyrroloaryls and pyrroloheteroaryls: Inhibitors of the HIV fusion/attachment, reverse transcriptase and integrase - Patel, Rahul V; Park, Se Won (Bioorganic & medicinal chemistry, 2015)
Heterocyclic compounds execute a very important role in drug design and discovery. This article provides the basic milestones of the research for pyrroloaryl and pyrroloheteroaryl based components targeting HIV viral replication cycle. Anti-HIV activity is elaborated for several classes of pyrrolo-compounds as pyrrolopyridines, pyrrolopyrimidines, pyrrolopyridazines, pyrrolobenzodiazepinones, pyrrolobenzothiazepines, pyrrolobenzoxazepinones, pyrrolophenanthridines, pyrroloquinoxalines, pyrrolotriazines, pyrroloquinolines, pyrrolopyrazinones, pyrrolothiatriazines, arylthiopyrroles and pyrrolopyrazolones targeting two essential HIV enzymes, reverse transcriptase and integrase as well as attachment/fusion of HIV virons to the host CD-4 cell. Such attempts were resulted in a discovery of highly potent anti-HIV agents suitable for clinical trials, for example, BMS-378806, BMS-585248, BMS-626529, BMS-663068, BMS-488043 and BMS-663749, etc. as anti-HIV attachment agents, triciribine, QX432, BI-1 and BI-2 as HIV RT inhibitors which are in preclinical or clinical development. Mechanism of action of compounds presented in this article towards the suppression of HIV attachment/fusion as well as against the activities of HIV enzymes reverse transcriptase and integrase has been discussed. Relationships of new compounds' molecular framework and HIV viral target has been overviewed in order to facilitate further construction of promising anti-HIV agents in future drug discovery process.
Keywords: objevování léků; HIV; pyrroly; HIV Integrase Inhibitors; HIV Fusion Inhibitors; Drug Discovery; Humans; inhibitory reverzní transkriptasy; HIV Integrase; Anti-HIV Agents; reverzní transkriptasa; Reverse Transcriptase Inhibitors; lidé; HIV-integrasa; Pyrroles; HIV infekce; Virus Replication; RNA-Directed DNA Polymerase; HIV Infections; inhibitory HIV fúze; replikace viru; inhibitory HIV-integrasy; látky proti HIV